Понятие “социальный круг” в истории социологии - Пипич, О. (Социология: теория, методы, маркетинг, 2000)
The term “social circle” is used primarily as an auxiliary term that helps to characterize a social structure, designate the belonging of individuals to a certain social group or another social formation. The one way to prove this term as sociological notion is historical sociological analysis of social circle as a scientific term and a notion. The main approaches in the history of sociology to the notion of “social circle” are under analysis in paper. The author examines theoretical interpretations of this notion by classics (F. Tönnies, G.Simmel) and neoclassics (P.Blau, J. Schepanski, analysts of network analyses). The article gives a summary and generalization of their ideas about social circle.